Cold adaptation overrides developmental regulation of sarcolipin expression in mice skeletal muscle: SOS for muscle-based thermogenesis? - Pant, Meghna (J Exp Biol, 2015)
Neonatal mice have a greater thermogenic need than adult mice and may require additional means of heat production, other than the established mechanism of brown adipose tissue (BAT). We and others recently discovered a novel mediator of skeletal muscle-based thermogenesis called sarcolipin (SLN) that acts by uncoupling sarcoendoplasmic reticulum Ca(2+)-ATPase (SERCA). In addition, we have shown that SLN expression is downregulated during neonatal development in rats. In this study we probed two questions: (1) is SLN expression developmentally regulated in neonatal mice?; and (2) if so, will cold adaptation override this? Our data show that SLN expression is higher during early neonatal stages and is gradually downregulated in fast twitch skeletal muscles. Interestingly, we demonstrate that cold acclimation of neonatal mice can prevent downregulation of SLN expression. This observation suggests that SLN-mediated thermogenesis can be recruited to a greater extent during extreme physiological need, in addition to BAT.